Clostridium difficile in Inflammatory Bowel Disease: A Retrospective Study. (4th October 2017) - Gillespie, William; Marya, Neil; Fahed, Julien; Leslie, Gregory; Patel, Krunal; Cave, David R.
Abstract : Aim . To investigate the epidemiology and risk factors of Clostridium difficile infections (CDI) in patients with inflammatory bowel disease (IBD). Methods . This is a retrospective study of patients diagnosed with IBD. 1006 charts were screened and 654 patients met the inclusion criteria. Patients were divided into 2 cohorts based on the presence of prior diagnosis of CDI. Statistical analysis with Pearson's chi-squared and two-sample t -test was performed. Results . The incidence of CDI among IBD patients was 6.7%. There was equal prevalence of CDI among Crohn's disease (CD) (n = 21, 49%) and ulcerative colitis (UC) (n = 22, 51%). IBD patients acquired CDI at a mean age of 42.7 years, with 56% of infections acquired in the community and only 28% associated with healthcare. Only 30% of IBD patients with CDI had prior antibiotic use, and 16% had prior steroid use. IBD patients were significantly more likely to require biologic therapy (57% versus 37%, p < 0.01 ) and have extraintestinal manifestations of IBD (43% versus 28%, p < 0.02 ). Conclusions . IBD patients are more susceptible to CDI at a younger age and often lack traditional risk factors. IBD patients with at least one CDI were more likely to require biologic therapy and had greater rates of extraintestinal manifestations.